Body Shape and Coloration of Silkworm Larvae Are Influenced by a Novel Cuticular Protein. Issue 3 (18th September 2017) - Xiong, Gao; Tong, Xiaoling; Gai, Tingting; Li, Chunlin; Qiao, Liang; Monteiro, Antónia; Hu, Hai; Han, Minjin; Ding, Xin; Wu, Songyuan; Xiang, Zhonghuai; Lu, Cheng; et al.
Abstract: Body shape and color patterns of insect larvae are fundamental traits for survival. Typically, transcription factors or members of signaling pathways... The genetic basis of body shape and coloration patterns on caterpillars is often assumed to be regulated separately, but it is possible that common molecules affect both types of trait simultaneously. Here we examine the genetic basis of a spontaneous cuticle defect in silkworm, where larvae exhibit a bamboo-like body shape and decreased pigmentation. We performed linkage mapping and mutation screening to determine the gene product that affects body shape and coloration simultaneously. In these mutant larvae we identified a null mutation in BmorCPH24, a gene encoding a cuticular protein with low complexity sequence. Spatiotemporal expression analyses showed that BmorCPH24 is expressed in the larval epidermis postecdysis. RNAi-mediated knockdown and CRISPR/Cas9-mediated knockout of BmorCPH24 produced the abnormal body shape and the inhibited pigment typical of the mutant phenotype. In addition, our results showed that BmorCPH24 may be involved in the synthesis of endocuticle and its disruption-induced apoptosis of epidermal cells that accompanied the reduced expression of R&R-type larval cuticle protein genes and pigmentation gene Wnt1 . Strikingly, BmorCPH24, a fast-evolving gene, has evolved a new function responsible for the assembly of silkworm larval cuticle and has evolved to be an indispensable factor maintaining the larval body shape and its coloration pattern. This is the first study to identify a molecule whose pleiotropic function affects the development of body shape and color patterns in insect larvae.